UZLUKSIZ TA’LIM TIZIMIDA DIDAKTIKA RIVOJINING ASOSIY YO‘NALISHLARI - Ibragimova, M.X. (SCIENCE and SOCIETY, 2021)
The article discusses and analyzes didactics in the system of continuing education, the main tasks of didactics, teaching methods in didactics, didactic tools, teaching methods, skills and abilities, theoretical and practical learning activities for teachers and students .